2021
DOI: 10.1088/1742-6596/2120/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Polymer Blend made from Post-used Styrofoam and Polypropylene for Fuse Deposition Modelling

Abstract: Fuse deposition modelling (FDM) has become a revolutionary manufacturing technology as it offers numerous advantages, including freedom of fabrication, mass customisation, fast prototyping, and cost-effectiveness. Thermoplastic material is commonly used as feedstock for FDM process. The current state of material development, the recycled plastic material also can be used as printing material for FDM machine. Expanded polystyrene (EPS) has been extensively used as packaging materials for many industries but rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
(18 reference statements)
2
7
0
Order By: Relevance
“…At same printing temperature, the printed specimen with rPS/rPP blend containing higher rPP content had more interlayers coalescence and minimized or absence of voids. A similar observation was also reported by William et al, [16] who found that the printed part with rPS/virgin PP blend at higher virgin PP content exhibited an absence of air gaps when examined under an optical microscope. As reported by Ariel Leong et al [7] and William et al, [16] the tensile strength of printed part with neat rPS and rPS/virgin PP with blend ratio of 50/50 were 34 and 25 MPa, respectively.…”
Section: Tensile Properties Of Printed Specimenssupporting
confidence: 88%
See 3 more Smart Citations
“…At same printing temperature, the printed specimen with rPS/rPP blend containing higher rPP content had more interlayers coalescence and minimized or absence of voids. A similar observation was also reported by William et al, [16] who found that the printed part with rPS/virgin PP blend at higher virgin PP content exhibited an absence of air gaps when examined under an optical microscope. As reported by Ariel Leong et al [7] and William et al, [16] the tensile strength of printed part with neat rPS and rPS/virgin PP with blend ratio of 50/50 were 34 and 25 MPa, respectively.…”
Section: Tensile Properties Of Printed Specimenssupporting
confidence: 88%
“…A similar observation was also reported by William et al, [16] who found that the printed part with rPS/virgin PP blend at higher virgin PP content exhibited an absence of air gaps when examined under an optical microscope. As reported by Ariel Leong et al [7] and William et al, [16] the tensile strength of printed part with neat rPS and rPS/virgin PP with blend ratio of 50/50 were 34 and 25 MPa, respectively. Zander et al [9] also reported that the print part with rPP/rPS with 50/50 blend ratio could achieve 23 MPa of tensile strength.…”
Section: Tensile Properties Of Printed Specimenssupporting
confidence: 88%
See 2 more Smart Citations
“…Utilizing recycled material acts as a circular economy strategy where plastic waste can be utilized as feedstock for FDM to reduce negative environmental impact. Thus, many researchers are putting great efforts on recycling plastic waste and turning it into FDM feedstock [3].…”
mentioning
confidence: 99%